2020
DOI: 10.1038/s41368-019-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint damage in K/BxN arthritic mice

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease affecting 1% of the world population and is characterized by chronic inflammation of the joints sometimes accompanied by extra-articular manifestations. K/BxN mice, originally described in 1996 as a model of polyarthritis, exhibit knee joint alterations. The aim of this study was to describe temporomandibular joint (TMJ) inflammation and damage in these mice. We used relevant imaging modalities, such as micro-magnetic resonance imaging (μMRI) and micro-compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Quantitative μCT analyses were performed using a Skyscan scanner 1276 μCT system (Bruker, Belgium) as previously described. 24 , 44 , 48 …”
Section: Methodsmentioning
confidence: 99%
“…Quantitative μCT analyses were performed using a Skyscan scanner 1276 μCT system (Bruker, Belgium) as previously described. 24 , 44 , 48 …”
Section: Methodsmentioning
confidence: 99%
“…In another study using the K/BxN model of spontaneous inflammation, increased expression of vascular endothelial growth factor and IL-17 and decreased expression of osteoprotegerin were observed in the limb joints, but not in the TMJ ( 25 ). In the same study with the K/BxN mouse model, the enlargement of the upper joint cavity in arthritic mice was confirmed by Magnetic Resonance Imaging, and only cartilage detachment of the TMJ surface was observed ( 26 ). In the present study, although the CAIA group showed increased osteoclast differentiation, there was no significant thinning of the chondrocyte layer or localization of lymphocytes.…”
Section: Discussionmentioning
confidence: 81%
“…In another study using the K/BxN model of spontaneous in ammation, increased expression of vascular endothelial growth factor and IL-17, and decreased expression of osteoprotegerin were observed in the limb joints, but not in the TMJ (23). In the same study with the K/BxN mouse model, the enlargement of the upper joint cavity in arthritic mice was con rmed by Magnetic Resonance Imaging, and only cartilage detachment of the TMJ surface was observed (24). In the present study, although the CAIA group showed increased osteoclast differentiation, there was no signi cant thinning of the chondrocyte layer or localization of lymphocytes.…”
Section: Effects Of Excessive Ms On the Mandibular Condyle In The Caia Mouse Modelmentioning
confidence: 83%